2017
DOI: 10.4103/0366-6999.217087
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging for the Assessment of Long Bone Tumors

Abstract: Background:Wide resection margins of osseous tumors are associated with a low incidence of local recurrence, making accurate measurement of the intraosseous extent of primary malignant long bone tumors is crucial. We compared the intraosseous tumor extent assessed by magnetic resonance imaging (MRI) with the gross specimen to evaluate the accuracy of MRI.Methods:A total of 255 patients with primary malignant tumors in the long bones were included. Using MRI, we defined the length of tumor as the distance from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In their study, estimation of tumor length was done on gross specimens whereas we had histopathology confirmation confirming the pathologic extent of disease as well. Tao et al showed a median difference of 2 mm (range: 0.1 cm to 1.5 cm) where the radiological disease extent was overestimated and a median difference of 5 mm (range: 0.1 cm to 1.8 cm) when the radiological disease extent was underestimated [25]. In our study when MRI overestimated the extent of disease, the mean was 1.79 cm with a standard deviation of 1.56 cm.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…In their study, estimation of tumor length was done on gross specimens whereas we had histopathology confirmation confirming the pathologic extent of disease as well. Tao et al showed a median difference of 2 mm (range: 0.1 cm to 1.5 cm) where the radiological disease extent was overestimated and a median difference of 5 mm (range: 0.1 cm to 1.8 cm) when the radiological disease extent was underestimated [25]. In our study when MRI overestimated the extent of disease, the mean was 1.79 cm with a standard deviation of 1.56 cm.…”
Section: Discussionmentioning
confidence: 39%
“…In Han et al's series, restricted to only osteosarcoma cases, the maximum underestimation was 0.9 cm and the maximum over estimation was 3.4 cm [23]. Tao's study [25] excluded tumors involving thin bones like the radius, ulna and fibula, whereas we have included all tumors in 100 consecutive cases. In their study, estimation of tumor length was done on gross specimens whereas we had histopathology confirmation confirming the pathologic extent of disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, T1W imaging may underestimate the tumor size. A recent study (15) found that the median tumor length on resection specimens was approximately 4 mm greater than that on T1W imaging. Conversely, T2W, STIR, and T1W fat suppression contrast-enhanced sequences have also been reported to overestimate the tumor size (16,17).…”
Section: Discussionmentioning
confidence: 98%
“…18,23 The use of MRI enables surgeons to accurately assess the extent of both intraosseous and extraosseous tumor involvement, which allows for an accurate preoperative evaluation and tumor resection. 15 At our institution, patients routinely had MRI imaging before chemotherapy and surgery to assess the response to neoadjuvant chemotherapy and determine the patient’s eligibility for limb-sparing surgery based on the MRI findings. Several factors are considered as contraindications to the use of the 3D-printed modular endoprosthesis, including tumor infiltration into major neurovascular structures, poor response to chemotherapy, involvement of adjacent bones, preexisting hindfoot and midfoot deformities, posterior tendon insufficiency, and vascular insufficiency preceding Achilles tendon pathology.…”
Section: Discussionmentioning
confidence: 99%